The phylogeny of Brachycorythis Lindl. and Neobolusia Schltr - Chuba, David (Department of Biological Sciences, 2017)
The monophyly of the genus Brachycorythis has been tested. The phylogeny of the African genera of Orchidinae - Orchideae - Orchidaceae (Schwartzkopffia, Brachycorythis, Neobolusia, Schizochilus, Dracomonticola, Holothrix and Bartholina is estimated with special attention to phylogenetic positions of Brachycorythis and Neobolusia. Pollen surfaces of twelve of the species are examined. Thirty-eight morphological and anatomical characters for 25 species of the species mentioned above are cladistically analysed and the stability of the different clades of the most parsimonious trees determined using various clade stability indices. The current delimitation of the Southern African Orchidae genera, with Neobolusia and all the other genera being independent from Brachycorythis is supported. Pollen surface ornamentation also shows the only species of Neobolusia examined for this (N. tysonii) as being quite different from the rest of the genera studied in having intectate pollen whereas the rest have semitectate pollen. This has further indicated support for the independence of Neobolusia from the genus Brachycorythis.